2009
DOI: 10.4102/sajip.v35i1.466
|View full text |Cite
|
Sign up to set email alerts
|

Psychological empowerment of employees in selected organisations in South Africa

Abstract: The objective of this study was to assess the construct validity and internal consistency of the Psychological Empowerment Questionnaire (PEQ) for employees in selected organisations in South Africa. A cross-sectional survey design with a convenient sample (N = 1405) was used. The PEQ was administered. Structural equation modelling confi rmed a four-factor model for the PEQ, consisting of competence, meaning, impact and self-determination. A cross-validation study confi rmed the construct equivalence of the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
2
14
0
2
Order By: Relevance
“…A higher score means a higher degree of psychological empowerment. Using structural equation modelling, Stander and Rothmann (2009) have confirmed the construct validity of the PEQ. They found that a four-factor structure (including meaning, competence, self-determination, and impact) fitted the data best.…”
Section: Measuring Instrumentssupporting
confidence: 60%
“…A higher score means a higher degree of psychological empowerment. Using structural equation modelling, Stander and Rothmann (2009) have confirmed the construct validity of the PEQ. They found that a four-factor structure (including meaning, competence, self-determination, and impact) fitted the data best.…”
Section: Measuring Instrumentssupporting
confidence: 60%
“…Similarly, high levels of absorption and experienced responsibility influence personal outcomes, which indicate that when employees feel they have control over their work environment, they will react with increased eagerness in doing their work. This is similar to the findings of Stander and Rothmann (2009). Research indicates that personal resources which refers to one's sense of being able to control the work and environment successfully (Hobfoll, Johnson, Ennis, & Jackson, 2003).…”
Section: Discussionsupporting
confidence: 87%
“…Taplin and Winterton (2007) found that a proactive approach to avoiding the costs involved in employee turnover is best and that serious investment in training may be the answer for many organisations. Stander and Rothmann (2009) reiterate this by identifying the development of employees as a key competence for managers. They point out that in order to be a good people developer, managers should be coached and developed to delegate authority, hold employees accountable for outcomes, lead by example, encourage subordinates, show concern for others' feelings, allow participative decisionmaking, share information and coach and mentor people.…”
Section: Discussionmentioning
confidence: 99%